A closer look at regional differences in euthanasia practices in the Netherlands - Wieke M. R. Ligtenberg; Theo A. Boer; A. Stef Groenewoud (Research in Health Services & Regions)
Abstract Background In research on practice variation, the body of knowledge on regional differences in the incidence of euthanasia is limited, and important questions have remained unanswered until now. Objective This paper aims to gain insight in the differences between euthanasia practices in high-incidence regions and low-incidence regions, by looking at (potential differences in) a) patient characteristics; b) timelines and the process of euthanasia; c) the setting in which euthanasia takes place; and d) morally relevant themes. Methods This explorative study uses a unique and fully anonymized dataset based on notes made by one of the authors (TAB) during a period of nine years in which he was an ethicist in a Dutch Euthanasia Review Committee. We analyzed these data using descriptive statistics and testing for statistical significance of differences in euthanasia practices in high-incidence regions and low-incidence regions. Results Some significant differences were found between high and low-incidence regions. Compared to low-incidence regions, high-incidence regions were characterized by patients being older at time of death, a shorter time span between patients’ first euthanasia request and their eventual death, patients more often having a GP as a consulting doctor, and euthanasia more frequently being the main dying means (as opposed to assisted suicide). The low incidence regions had somewhat younger patients, more patients with dementia, a longer life expectancy, more psychiatrists as consulting doctors, and more assisted suicides compared to the higher incidence regions. Conclusion This study adds new insights to the existing literature on (regional differences in) end-of-life care, with a specific focus on euthanasia. Until now, euthanasia practices have mainly been studied at national levels. National data show significant differences between regions. The black box of local practices has not been opened before. Our results have implications for practice, as they may inform discussions on appropriate care at the end of life in general, and euthanasia in particular.